RESOCIALIZING EFFECT OF PIMOZIDE ON CHRONIC INSTITUTIONALIZED SCHIZOPHRENIC PATIENTS - Soebagyo Hadinoto Soebagyo Hadinoto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1976)
A clinical trial of pimozide has been conducted, on 20 chronic institutionalized schizophrenic patients. using the